Investigating the Prevalence of Symptoms of Vibration-Related Illnesses Among Agricultural Machine Operators - Revilla, Josefa Angeli (Philippine Engineering Journal, 2025)
Abstract – The study assessed the prevalence of vibration-related symptoms and illnesses among agricultural machine operators, specifically length of years prior to the onset of symptoms of whole-body musculoskeletal disorder (MSD), probable existence of hand-arm vibration syndrome, and prevalence of carpal tunnel syndrome. It tested the correlation between various demographic characteristics of the operators and the occurrence and severity of the symptoms. One hundred operators from Tarlac and Laguna, Philippines, were invited to participate. The mean (± SD) age and farm-related experience are 44.92 ± 14.78 years old and 11.90 ± 10.17 years, respectively. Three questionnaires were used: the Extended Nordic Musculoskeletal Disorder (NMQ-E), the Cold Intolerance Symptom Severity, and the Boston Carpal Tunnel Syndrome Questionnaire. Data were gathered through group interviews and focus group discussions. Correlation analyses were performed to determine the influence of demographic variables to the occurrence and severity of symptoms. It was found that whole-body MSD symptoms are present in all covered body parts in the NMQ-E, with a maximum prevalence of 38% in the lower back and minimum prevalence of 12% in the elbows. The earliest average onset of MSD symptoms was observed in the shoulders after a mean of 9.0 operating years. The study also revealed that operators have experienced negative impacts on the hands and wrists, which manifested in the occurrence of diminished hand functions. Finally, statistical evaluations showed significantly moderate correlations between: (1) CTS symptoms with the number of hours operating a tractor in a week and number of years operating a tractor; (2) HAVS symptoms with the number of hours operating a tractor in a week, number of years operating a tractor, and the time of the day the equipment is being used. Hence, long-term and constant vibration exposure can potentially lead to the onset of MSD and significantly affect fundamental hand functions. Keywords: vibration-related illnesses, MSD, HAVS, CTS, long-term effects of vibration